Scoring rubric design to measure the ability to prove plane geometry problems not accompanied by image visualization - Ariawan, I Putu Wisna; Ardana, I Made; Divayana, Dewa Gede Hendra; Sugiarta, I Made (Jurnal Elemen, 2024)
Proof of the type of problem not accompanied by image visualization will require a longer flow and process than proof of the kind of problem accompanied by image visualization. The ability of students to prove problems, especially problems not accompanied by image visualization, must be adequately expressed and objectively. For that, we need an instrument that can reveal the ability to prove the case of these problems. This research has successfully designed a scoring rubric that can be explicitly used to measure students' proving abilities on problems not accompanied by image visualization. Aspects developed in the scoring rubric include making image visualizations according to the information in the questions. These include sub-aspects of image accuracy and completeness of labels, initial steps of proving, preparation of conjectures, flow of proving, and support for valid arguments for statements made. Based on the validation from the experts, the scoring rubric developed was declared valid and ready to be used to measure the student's proving ability on plane geometry, proving problems not accompanied by image visualization.